Evaluating quality and price dynamics of wood pellets in the Portuguese market: Impacts of geopolitical and economic factors - Rui Pinho; Miguel Oliveira; Bruno Manuel Mendes Teixeira; Amadeu Duarte da Silva Borges (Energy Strategy Reviews)
The 1970s oil crisis led to a chase for alternative fossil fuel alternatives in Europe and the wood pellets were invented, though only in de 1990s gained acceptance as a dependable source of energy and needed standards to ensure quality and fair-trade conditions. Our study focused on the standard ISO 17225-2, a worldwide standard focused on evaluating pellet quality. For this work, data about prices of pellets in Germany, France, Austria and Portugal were collected. Raw materials are limited in Europe as a result of the conflict between Russia and Ukraine, which raises wood pellets prices. Portuguese prices are oddly high compared to the rest of Europe as Portuguese producers prefer to export instead of internal consumption. These findings uncovered that 3 brands of pellets don't meet the requirements for A1 class pellet.